Assessing the Effects of Moderate to High Dosage of Astaxanthin Supplementation on Lipid Profile Parameters—A Systematic Review and Meta-Analysis of Randomized Controlled Studies - Laurindo, Lucas Fornari; Rodrigues, Victória Dogani; Carneiro, Dennis Penna; Marangão Filho, Luiz Sérgio; de Souza Bastos Mazuqueli Pereira, Eliana; Tofano, Ricardo José; Chagas, Eduardo Federighi Baisi; dos Santos Haber, Jesselina Francisco; Caracio, Flávia Cristina Castilho; Moreira, Letícia Zanoni; Valenti, Vitor Engrácia [UNESP]; Barbalho, Sandra Maria (MDPI, 2025)
Background/Objectives: Astaxanthin, a xanthophyll carotenoid, has garnered significant interest due to its benefits with regard to dyslipidemia. This multifaceted functional food ingredient modulates several key enzymes associated with lipid regulation, including HMG-CoA reductase, CPT1, ACCβ, and acyl-CoA oxidase. It influences key antioxidant molecular pathways like the Nrf2, limiting dyslipidemia occurrence and regulating liver cholesterol uptake through the modulation of liver lipid receptors. Due to the current lack of systematic reviews and meta-analyses assessing moderate to high dosages (6-24 mg/d) of astaxanthin supplementation on lipid dysregulation, the present manuscript aims to fill this gap in the literature. Methods: Following the PRISMA guidelines, we included eight studies comprising eleven results from the PubMed, Springer Link, Science Direct, Cochrane, and Google Scholar databases. The Jamovi (Version 2.6.26, Solid) software was utilized for statistics. Our primary objective was to assess in detail the effects of astaxanthin on LDL-C, HDL-C, triglyceride, and total cholesterol levels. Results: The meta-analysis concludes positive effects of astaxanthin (6-20 mg/d) on HDL-C (0.4200; 95% CI: 0.1081 to 0.7319) and triglyceride (-0.3058; 95% CI: -0.5138 to -0.0978) levels. Unfortunately, astaxanthin (6-20 mg/d) does not appear to significantly influence LDL-C (-0.0725; 95% CI: -0.3070 to 0.1620) and total cholesterol (-0.0448; 95% CI: -0.3369 to 0.2473) levels. Regarding HDL-C, improvements were observed from 55 ± 8 mg/dL (pre-intervention) to 63 ± 8 mg/dL (post-intervention) (p < 0.01) in the 12 mg/d of astaxanthin groups. In the assessment of triglyceride levels, results show a decrease from 151 ± 26 mg/dL (pre-intervention) to 112 ± 40 mg/dL (post-intervention) (p < 0.01) for 18 mg/d astaxanthin supplementation. Conclusions: Further research is necessary to fully harness the potential of astaxanthin, which includes assessing astaxanthin in different subsets of patients, using a GWAS, and in combination with other nutraceuticals to understand the compound's effectiveness with regard to varying health conditions, genetic and epigenetic factors, and synergistic effects with other compounds.